The influences of green product development (GPD) on green product development performance in Malaysia: The moderating role of green creativity - Tan, Hwee Chin (Universiti Malaysia Sarawak (UNIMAS), 2015)
The purpose of this study was conducted to investigate the relationship between green product development and green product development performance with the green creativity as moderator. A total of 103 sets of questionnaire were distributed to available finn that related to green product development in Malaysia randomly. Data collection is done via the nonprobability sampling method. Based on this research, the results revealed that green dynamic capability and green product innovation are positively related to financial performance and competitive advantage. Besides, the results showed that green transfonnational leadership and green process innovation are not positively related to financial performance and competitive advantage. Last but not least, the results also revealed that green creativity is partially positive moderates the relationship between green product development and green product development performance. However, green creativity has direct positive impacts on financial performance and competitive advantage.